Managing social issues a public values perspective - edited by Peter Leisink (Cheltenham Edward Elgar, 2013)
This book examines how governments, non-profit and private organizations, and local networks understand the connections between public values and social issues.
Includes bibliographical references and index.
Keywords: Social policy